2020
DOI: 10.3390/toxics8020044
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Assessment of Cadmium in Female Farmers in Cadmium-Polluted Areas in Northern Japan

Abstract: Akita prefecture is located in the northern part of Japan and has many cadmium-polluted areas. We herein performed an exposure assessment of cadmium in 712 and 432 female farmers in two adjacent cadmium-polluted areas (A and B, respectively), who underwent local health examinations from 2001–2004. We measured cadmium concentrations in 100 food items collected from local markets in 2003. We then multiplied the intake of each food item by its cadmium concentration in each subject to assess cadmium intake from fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Table 1 summarizes also food products that contributed significantly to total intake of Pb and the estimated intake levels of the metal among adult consumers in China [89][90][91], Korea [92], Germany [100], Spain [95] and the U.S. [84]. Furthermore, Cd intake levels estimated for consumers in Sweden [88] France [101], Belgium [102] and a region with Cd pollution of Japan [103] are provided. U.S. [84,97] n = 14,614 FDA 2014-2016 total diet study Average consumers: 4.63 µg/day.…”
Section: Total Diet Studies and Dietary Intake Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 summarizes also food products that contributed significantly to total intake of Pb and the estimated intake levels of the metal among adult consumers in China [89][90][91], Korea [92], Germany [100], Spain [95] and the U.S. [84]. Furthermore, Cd intake levels estimated for consumers in Sweden [88] France [101], Belgium [102] and a region with Cd pollution of Japan [103] are provided. U.S. [84,97] n = 14,614 FDA 2014-2016 total diet study Average consumers: 4.63 µg/day.…”
Section: Total Diet Studies and Dietary Intake Estimatesmentioning
confidence: 99%
“…Thus, the utility of dietary intake estimates in health risk assessment is questionable. In another example, the total diet study undertaken in two areas of Japan affected by Cd pollution reported the median Cd intake levels in female farmers residing in the two areas as 47.8 and 55.7 µg/day [ 103 ]. These estimated Cd intake levels in Cd-polluted areas were lower than the FAO/WHO tolerable intake level, but adverse health effects were observed [ 103 ].…”
Section: Exposure Sources and Dietary Intake Estimatesmentioning
confidence: 99%
“…In this Special Issue, entitled “Toxic Metals, Chronic Diseases and Related Cancers”, there are 19 published manuscripts, including reports of environmental exposure monitoring [ 1 , 2 ] and food safety surveillance [ 3 , 4 ]; reviews focusing on health risks of chronic exposure to cadmium and lead [ 5 ], experimental studies on the toxicity of cadmium, lead or mercury in gonads [ 6 ], and evidence that cadmium exposure may be one of the environmental factors contributing to hyperglycemia, insulin resistance and diabetes [ 7 ]; a mathematical model of the oral glucose tolerance test [ 8 ]; epidemiological studies examining health impacts of cadmium, lead, and mercury [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]; and reports concerning the immunotoxicity of high exposure to lead [ 16 ], the effects of cadmium on protein reabsorption by kidney tubular epithelial cells [ 17 ], the cytotoxicity of hexavalent chromium [ 18 ], and the carcinogenicity of aluminum in vivo [ 19 ].…”
mentioning
confidence: 99%
“…Horiguchi et al report cadmium intake levels among women living in two areas of Japan with recognized cadmium pollution in excess of the current tolerable intake level of 0.83 µg/kg bw/d [ 3 ]. In one area where rice cadmium content ranged from below 0.02 to 0.971 mg/kg, the average cadmium intake was 55.7 µg/d (1.03 µg/kg body weight per day).…”
mentioning
confidence: 99%
“…Horiguchi et al (2020) stated that the mean Cd content of rice collected from area A (Odate city) and area B (Kazuno city and Kosaka town) in Japan were 0.158 and 0.109 mg/kg, respectively. Moreover,Chu et al (2021) stated that Vietnamese rice samples contained a mean of 0.111±0.105 mg/kg Mohamed et al (2017).…”
mentioning
confidence: 99%